Soziales Lernen im Sachunterricht – Begriffsklärungen, Umsetzungsmöglichkeiten und fachdidaktische Reflexion. Ein Seminarkonzept im Master of Education - Diederich, Julia (Soziales Lernen in der Grundschule und Sachunterricht. Theoretische Grundlagen, empirische Befunde und didaktische Implikationen)

Zur Adaptionsfähigkeit und Dynamik von jüdischen Mahlritualen in antiken und modernen Krisenzeiten - Bergmann, Claudia Dorit (Ethische Perspektiven zum Speisen in Antike und Gegenwart. Kontexte und Normen neutestamentlicher Ethik XV)

Rezension zu: Susan Weingarten, Ancient Jewish Food in its Geographical and Cultural Contexts. What's Cooking in the Talmuds - Bergmann, Claudia Dorit (Journal for the Study of Judaism)

Religious Diversity and Global Concerns

CommuniAction – Kommunikation und Verständigung spielerisch fördern und gestalten: eine praxisorientierte Handreichung für Akteur:innen in Innovations- und Verbundprojekten in der beruflichen Bildung - Breuing, Friederike; Daniel-Söltenfuß, Desiree; Kremer, H.-Hugo; Kückmann, Marie-Ann

New Quick And Easy Publication - Will be edited by LibreCat team - Rebekka Gallusser (Quick And Easy Journal Title)

Die Ausbildung von morgen gestalten: mit 5G und für 5G. Unterrichtliche Anwendungsbeispiele für das Lernen mit 5G und für 5G an kaufmännischen und gewerblich-technischen Berufskollegs aus Ostwestfalen-Lippe - Beutner, Marc; Koppius, Sebastian Niklas; Schäfers, Johannes; Temmen, Katrin (bwp@ Spezial HT2025: Nachhaltig – Digital – Chancengerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf)
Keywords: 5. Generation des Mobilfunkstandards (5G); Digitaler Reifegrad im Berufsschulunterricht; Best-Practice-Beispiele

Role of Irradiance in Light-Activated In2O3Gas Sensors: Why More Light Is Not Always Better - Voth, Sven; Zhao, Zhenyu; Baier, Dominik; Glass, Alexandra; Elgabarty, Hossam; Sandberg, Oskar J.; Grundmeier, Guido; Tiemann, Michael; Smått, Jan-Henrik; Anttu, Nicklas; de los Arcos, Teresa; Weinberger, Christian (ACS Sensors)
Light-assisted metal oxide-based chemiresistive gas sensors are widely explored for operation at relatively low temperatures, yet the investigation of the role of irradiance, as opposed to wavelength, remains underrepresented. Here, we systematically quantify the irradiance-dependent behavior of ordered mesoporous In2O3 under visible light illumination. Photoconductivity measurements reveal two distinct irradiance regimes consistent with trap-limited transport at low power and recombination- or saturation-limited transport at high power. Gas sensing experiments towards CO and H2 show a pronounced non-monotonic response, reaching maximum responses of 0.74 for 135 ppm CO at 67 mW cm−2 and 0.64 for 90 ppm H2 at 11 mW cm−2, followed by strong suppression at higher irradiance. Illumination also accelerated the response kinetics. At 60 ppm, t90 decreases from 96 to 12 s for CO and 141 to 27 s for H2, corresponding to an 8- and 5-fold faster response time, respectively. Near-ambient pressure-XPS under controlled atmosphere and density functional theory calculations indicate defect-mediated excitation. Oxygen vacancy states and illumination-induced modification of surface oxygen species govern this behavior. The results establish irradiance as a critical mechanistic parameter that determines whether In2O3 operates in a surface-controlled or bulk photoconductive regime. These findings highlight the need to explicitly optimize and report irradiance in illuminated gas sensor studies, and not only the power consumption of the light source.
Keywords: resistive gas sensing; indium oxide; photoactivation; irradiance; photoconductivity; charge carrier dynamics; oxygen vacancies

Can I Help to Explain That? A Conceptual Model Integrating Social Cognition and Intentional Stance Theories for Agentic XAI Design - Rehmer, Lennart; Grieger, Nicole; Trier, Matthias; Kundisch, Dennis (Proceedings of the 21. Internationale Tagung Wirtschaftsinformatik)

Structuring the Use of Virtual Reality in Human Behavior Research: A Taxonomy of Empirical Studies - Rehmer, Torben; Rehmer, Lennart; Kundisch, Dennis; Trier, Matthias (Proceedings of the 21. Internationale Tagung Wirtschaftsinformatik)

Mind the Gender Pitch Gap: The Effect of Regulatory Focus and Tense Orientation on Startup Funding - Hansmeier, Lars; Grieger, Nicole; Kundisch, Dennis (Proceedings of the 21. Internationale Tagung Wirtschaftsinformatik, Student Track)

Reframing school leadership for the digital age - Cochrane, Janet; Tan, Seng Chee; Phillips, Michael; Eickelmann, Birgit; Kral, Marijke; Chammon, Jacob; Pangeni, Shesha Kanta (Computers and Education Open)

Digital Futures Between Participatory Digital Democracy and Participatory Digital Fascism - Fuchs, Christian; Friesch, Kevin; Museba, Joel (Policy & Internet)
This paper explores one of the defining political questions of the twenty‐first century: will digital technologies strengthen democracy or accelerate new forms of authoritarianism and fascism? Against the backdrop of platform capitalism, AI‐driven communication, surveillance infrastructures, disinformation and democratic crisis, the study asks how experts in digital democracy assess the present condition and possible futures of digital society. To address this question, the paper draws on the Futures of Digital Democracy Survey (FDDS), a two‐round international expert survey involving researchers, practitioners and civil society actors working in the fields of digital democracy, media, Internet governance and digital society. Combining futures research, scenario analysis, and qualitative and quantitative content analysis, the study investigates competing trajectories of digital development ranging from participatory digital democracy to corporate and state‐controlled digital fascism. The findings reveal a profound tension at the heart of contemporary digital society: while respondents overwhelmingly imagine an ideal future democracy in participatory and deliberative terms—centred on citizens’ assemblies, digital participation, public‐service Internet platforms and democratic AI—they simultaneously express deep pessimism about the actual direction of digital capitalism and platform power. Experts consider authoritarian and fascistic digital futures significantly more likely than democratic ones. The paper analyses these contradictions by examining the relationship between deliberative democracy, constitutional rights, platform governance, digital commons, public service media, AI, surveillance and the political economy of Big Tech. It argues that democracy in the digital age can only survive if participatory and deliberative digital structures are institutionally combined with constitutional safeguards, public ownership, democratic regulation and the defence of human rights. By bringing together debates on digital democracy, authoritarianism, political economy and digital futures, the paper offers both a critical diagnosis of the contemporary digital condition and a normative vision of democratic alternatives in the age of AI and platform capitalism.

Merkmale guter inklusiver Schulen – Zusammenhänge auf Lehrkraft-Ebene - Wohlhas, Verena; Böhm-Kasper, Oliver; Neumann, Phillip (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- und Professionsentwicklung)
Der Beitrag beschäftigt sich mit der Frage, ob die Merkmale guter inklusiver Schulen – verstanden als Schulentwicklungsinstrument – mit der Arbeitszufriedenheit und den Selbstwirksamkeitsüberzeugungen von Lehrkräften in inklusiven Gesamt- und Sekundarschulen zusammenhängen. Dazu werden Daten aus dem BMBF-geförderten Projekt BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) von N = 119 Lehrkräften analysiert. Die Ergebnisse zeigen, dass die Merkmale guter inklusiver Schulen einen großen Teil der Varianz in der Arbeitszufriedenheit aufklären. Die kollektive Selbstwirksamkeitsüberzeugung korreliert stark mit den Merk-malen guter inklusiver Schulen und der Arbeitszufriedenheit der Lehrkräfte. Für die individuelle inklusionsbezogene Selbstwirksamkeitsüberzeugung zeigen sich itemspezifische Befunde, die diskutiert werden. Implikationen für die schulische Praxis werden abgeleitet.
Keywords: Arbeitszufriedenheit; Inklusion; Merkmale guter inklusiver Schulen; Selbstwirksamkeit; kollektive Selbstwirksamkeitsüberzeugung

Entwicklungslinien der beruflichen Fachrichtung Sozialpädagogik und einer Didaktik der Sozialpädagogik: Perspektiven einer scientific community im Werden - Bobe, Anna; Göddertz, Nina; Karber, Anke; Paesche, Moritz; Schmökel, Michelle Jaquelina; Schwertfeger, Anja; Seltrecht, Astrid (bwp@ Spezial HT2025: Nachhaltig – Digital – Chancengerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf)

ABIS 2026: The Effects of the Adaptive Web on Society - Stojko, Laura; Herder, Eelco; Strecker-Bischoff, Jannis; Sänger, Julia Seitz; Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam (Companion Publication of the 2026 18th ACM Web Science Conference, WebSci Companion 2026, Braunschweig, Germany, May 26-29, 2026)

bwp@ Spezial HT2025: Nachhaltig – Digital – Chancen gerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf

Stereotype Darstellungen im Bild. Analyse von Bildmaterial digital verfügbarer Unterrichtsmaterialien - Schmidt, Rebecca; Drath, Hannah; Steinhardt, Isabel (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Lehrer:innen nutzen und veröffentlichen Unterrichtsmaterial auf verschiedenen Plattformen. Da diese Materialien, anders als Schulbücher, kein Qualitätssicherungsverfahren durchlaufen, wird aktuell die Frage nach der Verantwortung für die Qualitätssicherung dieses Materials diskutiert. Abbildungen von Menschen im Unterrichtsmaterial transportieren soziokulturelle und pädagogische Inhalte, die eine kritische Prüfung erfordern. Dieser Beitrag adressiert die Frage, welche Differenzkonstruktionen und Stereotypisierungen im Bildmaterial von digital verfügbarem Unterrichtsmaterial vorhanden sind. Verwendet wurde ein Materialkorpus drei verschiedener Plattformen mit Unterrichtsmaterialien der Sekundarstufe 1 (5. – 10. Klasse) mit 329 Bildern von Menschen (Zeichnungen und Fotografien). Dieser wurde analysiert in Bezug auf die deskriptive Häufigkeit der Darstellung bestimmter Personengruppen sowie qualitativ und intersektional mit der hermeneutischen Sequenzanalyse. Zentrale Ergebnisse sind, dass vor allem Personen dargestellt werden, die in maximal einer Dimension von der weissen, heterosexuellen, nicht behinderten Norm abweichen. Darstellungen von sichtbaren Behinderungen und People of Color (BIPoC) kommen kaum vor. Diversität wird vereinzelt in Gruppenbildern dargestellt, jedoch nicht in Familienbildern. Othering und negative emotionale Konnotationen sind in den Darstellungen erkennbar, wenn z. B. Schwarzsein als Abweichung von der Norm verstanden wird, Körperproportionen verzerrt oder Sportler:innen als unsicher dargestellt werden. Die Analyse von digital bereitgestelltem Unterrichtsmaterial macht deutlich, dass ähnliche Problematiken zu beobachten sind, wie sie durch die Schulbuchforschung für Schulbücher beschrieben werden.

Spatially Uniform and Defect‐Tolerant Plasmonic Responses in 3D Printed Gold Nanoparticle Assemblies - Devaraj, Vasanthan; Kwak, Sunghyun; Kim, Hyeongjip; Sung, Sang‐Keun; Lee, Jong‐Min; Zentgraf, Thomas; Kim, Won‐Geun (Laser & Photonics Reviews)
Three‐dimensional (3D) assemblies of gold nanoparticles (AuNPs) offer a rich platform for plasmonic coupling and near‐field engineering, yet their optical behavior is often complex due to structural disorder and fabrication‐induced variability. Here, we present a systematic optical investigation of large‐scale 3D AuNP assemblies fabricated via meniscus‐guided assembly, focusing on the reproducibility, spatial uniformity, and mode evolution of their plasmonic responses. Spatially‐resolved dark‐field scattering measurements reveal that high‐aspect‐ratio AuNP pillars exhibit uniform scattering spectra along their height and across different pillars, despite variations in geometry and structure. Electromagnetic simulations suggest that this robustness arises from a collective many‐particle plasmonic response that remains optically active despite structural perturbations. The corresponding near‐field and surface‐charge distributions remain spatially distributed under representative structural perturbations, consistent with volumetric averaging across the three‐dimensional assembly. Building on this robust platform, we introduce compositional modulation through a core–satellite architecture by incorporating smaller AuNPs. This yields a composition‐dependent spectral redistribution, including the emergence of an additional long‐wavelength spectral feature in the core–satellite assemblies. Wavelength‐dependent surface‐enhanced Raman scattering measurements reveal contrasting responses under 633 and 785 nm excitation, reflecting redistribution of local plasmonic coupling pathways. These results provide process‐enabled guidelines for using meniscus‐guided 3D‐nanoprinting to realize robust nanoparticle assemblies.

“The city isn’t uploading me to TikTok”: Exploring Privacy Attitudes towards Data Collection in Urban Public Spaces - Todt, Julian; Kablo, Emiram; Morsbach, Felix; Arias Cabarcos, Patricia; Strufe, Thorsten (Proceedings on Privacy Enhancing Technologies)
Smart cities promise safer streets, smoother traffic, and more efficient services, enabled by dense networks of urban sensors. Yet this infrastructure, often unnoticed by citizens, introduces pervasive privacy risks, from tracking, profiling, and sensitive inferences to subtle forms of self-censorship. Despite widespread deployment, little is known about how the public understands and perceives these sensing systems. To address this gap, we present an intervention based user study (n = 172) in which participants are exposed to data collection by six urban sensors, including cameras and alternative technologies commonly framed as privacy-preserving. Participants encounter either the sensors alone or sensors accompanied by real-time data visualizations. Our results reveal widespread misunderstanding of some sensors (radar, LiDAR, Wi-Fi, depth, and thermal imaging sensors), particularly their capacity for identification and for attribute inferences such as gender or age. We also identify persistent misconceptions, including the belief that Wi-Fi poses privacy risks only when users connect to public networks. While making sensors visible and visualizing collected data improves privacy awareness, these measures alone are not enough for citizens to understand the actual risks of urban sensing. We derive recommendations for privacy-respecting smart city environments grounded in citizens’ informational needs and expectations.